An Insight Into the Modulatory Effects and Mechanisms of Action of Phyllanthus Species and Their Bioactive Metabolites on the Immune System - Jantan, Ibrahim; Haque, Md. Areeful; Ilangkovan, Menaga; Arshad, Laiba (Frontiers in Pharmacology, 2019)
Phyllanthus species (family; Euphorbiaceae) have been intensively studied for their immunomodulating effects due to their wide-ranging uses to treat immune-related diseases in indigenous medicine, which are primarily lack of scientific basis. The focuses of this review are on the significance of Phyllanthus species and their bioactive metabolites particularly corilagin (1), geraniin (2), gallic acid (3), phyllanthin (4), hypophyllanthin (5), ellagic acid (6), phyltetralin (7), niranthin (8), catechin (9), quercetin (10), astragalin (11), and chebulagic acid (12) in the modulation of both innate and adaptive immune systems through various mechanisms and their possible therapeutic benefits for treatment of immune-related diseases. We have compiled all significant findings published in the literature, and the data were analyzed critically to provide perspectives and directions for future research for the plants as a prospective source of novel immunomodulating agents. Various Phyllanthus species particularly Phyllanthus amarus, Phyllanthus emblica, Phyllanthus niruri, and Phyllanthus urinaria have been documented to possess significant immunomodulatory effects. However, the possible challenges encountered by the application of extracts of various Phyllanthus species and their bioactive constituents as immunomodulators need to be addressed. Most reports on the biological and pharmacological studies of the plants were based on crude extracts. The extracts were not chemically characterized, and the contributions of their chemical constituents to the bioactivities were not identified. The underlying mechanisms involved in the immunomodulatory effects of the Phyllanthus species were not indepthly studied due to limitations in terms of design, conduct, and interpretation. Extensive experimental and preclinical studies on the immunomodulating potential of Phyllanthus species should be carried out to provide sufficient data to prove that their traditional uses are inherently effective and safe and will allow clinical trials to be pursued for their further development as therapeutic agents to treat immune-related disorders.